Perancangan Game Animasi Teka Teki Silang Menggunakan Adobe Flash CS6 - Jaria Rama Triyanti (Journal of Student Development Information System (JoSDIS), 2022)
Computer technology is one of the technologies that can help speed up human work.Computer technology has been applied in various fields including education, health, offices, telecommunications, business, military and so on, as well as in the world of entertainment. One form of entertainment including games, games are very rapidly developing along with the advancement of computer technology. Games are very much in demand both from children, teenagers to adults. The Game itself is of various types, one of the games that are loved and educational for children and adolescents at this time is a quiz-shaped game. Flash is a software that is generally used to create an animation, but currently flash is widely used for other things, such as the creation of websites, games, and so forth.The purpose of this final project is to design animated games for children and adults to train memory and outside insight about the computer. Children and adults to never get bored to learn, thus helping children and adults know technology and provide convenience to children and adults to learn general knowledge of technology and about computers. From the results of the research can be seen that the game animation crossword general knowledge about basic computer levels based on flash can know more clearly about adobe Flash CS6.